Working University Students in Riau Archipelago: Dual Role and Depression - Nurul Retno Nurwulan; Gjergji Selamaj (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
University students working and studying at the same time for various reasons. The aim of the study is to review the impact of studentsâ€™ dual role as students and workers on the depression rate of working university students in Batam, Indonesia. A comprehensive review of the literature revealed that working while studying does not necessarily affect studentsâ€™ academic performance. However, depression is the most common health problem in university students. However, working students tend to have higher depression rate than non-working students. Depression in students may be the cause of the high dropout rate in Batam. It is important to administer depression-prevention intervention as early as possible, since the first- and second-year students are the most likely to get depressedÂ Beragam alasan melatarbelakangi mahasiswa bekerja selama berkuliah. Penelitian ini mengulas dampak peran ganda sebagai mahasiswa dan pekerja kecenderungan depresi pada mahasiswa bekerja di Batam, Indonesia. Ulasan komprehensif dari literatur dan observasi langsung menunjukkan bahwa bekerja sambil berkuliah tidak mempengaruhi kinerja akademis mahasiswa. Meskipun demikian, mahasiswa bekerja cenderung memiliki tingkat depresi yang lebih tinggi daripada mahasiswa yang tidak bekerja. Depresi pada mahasiswa dapat menjadi penyebab tingginya tingkat dropout di Batam. Melakukan intervensi pencegahan depresi pada mahasiswa sedini mungkin merupakan hal yang sangat penting dikarenakan mahasiswa tingkat pertama dan kedua adalah yang paling rentan terhadap depresi.